Conformal LATP surface engineering for Ni-rich cathodes: enhancing interfacial stability and thermal safety in lithium-ion batteries - Xu, Yunli; Wang, Lan; Geng, Jie; Ma, Lin; Qiu, Jia; Han, Gaige (Frontiers in Chemistry, 2025)
Enhancing the interfacial stability and thermal safety of Ni-rich layered oxide cathodes remains a critical challenge for the development of high-energy lithium-ion batteries. Herein, a conformal NASICON-type Li1.3Al0.3Ti1.7(PO4)3 (LATP) coating was applied to the surface of NCM811 particles via a facile wet-chemical method followed by thermal treatment. Transmission electron microscopy and energy-dispersive X-ray spectroscopy confirmed the uniform distribution of an amorphous LATP layer (∼5–10 nm) on the cathode surface without penetrating the bulk. This LATP coating effectively suppressed interfacial side reactions, stabilized the electrode–electrolyte interface, and mitigated transition metal dissolution, resulting in significantly improved cycling stability and lower impedance growth during electrochemical operation. Importantly, comprehensive thermal runaway evaluations using pouch cells revealed that LATP modification increased the onset (T1) and trigger (T2) temperatures, extended the delay time to thermal runaway (Δt1), and reduced the maximum temperature (T3) and mass loss during abuse conditions. These improvements were preserved even after cycling-induced degradation (75% state of health), underscoring the coating’s robustness. This study demonstrates a viable surface engineering strategy that synergistically enhances the electrochemical performance and intrinsic thermal safety of Ni-rich cathodes, providing valuable insights for the design of next-generation safe, high-energy lithium-ion batteries.